A systematic scoping review of communication skills training in medical schools between 2000 and 2020. (2nd September 2022) - Venktaramana, Vaishnavi; Loh, Eleanor Kei Ying; Wong, Clarissa Jing Wen; Yeo, Jun Wei; Teo, Andrea York Tiang; Chiam, Celest Sin Yu; Foo, Dillon Jie Ming; Teo, Faith; Liang, Jonathan; Raveendran, Vijayprasanth; Chng, Luke Cheng Lin; Xiao, Shiwei; et al.
Abstract: Background: Communication skills training (CST) remains poorly represented and prioritised in medical schools despite its importance. A systematic scoping review (SSR) of CST is proposed to better appreciate current variability in their structure, content, and assessment. This is to guide their future design in medical school curricula. Methods: The Systematic Evidence-Based Approach (SEBA) was used to guide concurrent SSRs of teaching and assessment in CST. After independent database searches, concurrent thematic and content analysis of included articles were conducted separately. Resultant themes/categories were combined via the jigsaw perspective to provide a more holistic view of the data. These were then compared to tabulated summaries of the included articles to create funnelled domains. Results: 52, 300 papers were identified, 150 full-text articles included, and four funnelled domains were identified: Indications, Design, Assessment, and Barriers and Enablers of CST. CSTs confer numerous benefits to physicians and patients. It saw increased confidence, improved diagnostic capabilities and better clinical management, as well as greater patient satisfaction and treatment compliance. Skills may be divided into core, prerequisite competencies, and advanced skills pertinent to more challenging and nuanced scenarios – such as population or setting-specific situations. CST teaching and assessment modalities were found to align with Miller's Pyramid, with didactic teaching gradually infused with experiential approaches to enhance their understanding and integration. A plethora of CST frameworks, teaching and assessment methods were identified and are presented together. Conclusion: While variable in approach, content and assessment, CST in medical schools often employ stage-based curricula to instil competency-based topics of increasing complexity throughout medical school education. This process builds on the application of prior knowledge and skills, influencing practice and, potentially, the students' professional identity formation. In addition, the institution plays a critical role in overseeing training, ensuring longitudinal guidance and holistic assessments of the students' progress.